Identification of Biomarkers Related to the Efficacy of Radiotherapy in Pancreatic Cancer - Caxali, Gabriel Henrique [UNESP]; Brugnerotto, Laiza [UNESP]; Esgoti Aal, Mirian Carolini [UNESP]; Castro, Camila Ferreira Bannwart [UNESP]; Delella, Flavia Karina [UNESP] (Anticancer Research USA, 2023)
Background/Aim: Pancreatic cancer (PC) has one of the highest mortality rates, with an overall five-year survival rate of only 7%. When diagnosed, PC is limited to the pancreas in only 20% of patients, whereas in 50% it has already metastasized. This is due to its late diagnosis, which makes the treatments used, such as radiotherapy, difficult, and reduces survival rates. Therefore, the importance of this study in detecting genes that may become possible biomarkers for this type of tumor, especially regarding the human secretome, is highlighted. These genes participate in pathways that are responsible for tumor migration and resistance to therapies, along with other important factors. Materials and Methods: To achieve these goals, the following online tools and platforms have been expanded to discover and validate these biomarkers: The Human Protein Atlas database, the Xena Browser platform, Gene Expression Omnibus, the EnrichR platform and the Kaplan-Meier Plotter platform. Results: Our study adopted a methodology that allows the identification of potential biomarkers related to the effectiveness of radiotherapy in PC. Inflammatory pathways were predominantly enriched, related to the regulation of biological processes, primarily in cytokinederived proteins, which are responsible for tumor progression and other processes that contribute to the development of the disease. Conclusion: Radiotherapy treatment demonstrated greater efficacy when used in conjunction with other forms of therapy since it decreased the expression of essential genes involved in several inflammatory pathways linked to tumor progression.
Keywords: bioinformatics,radiotherapy; biomarker; Pancreatic cancer; resistance; secretome